Wage-setting Behavior in France: Additional Evidence from an Ad-hoc Survey - Jérémi Montornès; Jacques-Bernard Sauner-Leroy (Journal of Banking and Financial Economics)
We investigate the wage-setting behavior of French companies using an ad-hoc survey specifically conducted for this study. Our main results are the following. i) Wages are changed infrequently. 75% of firms change their wages once a year. Wage changes occur at regular intervals during the year and are concentrated in January and July. ii) We find a lower degree of downward real wage rigidity and nominal wage rigidity in France compared to the European average. iii) About one third of companies have an internal policy to grant wage increases according to inflation. iv) When companies are faced with adverse shocks, the latter are partially transmitted into prices. Companies also adopt cost-cutting strategies. The wage of newly hired employees plays an important role in this adjustment.